Eksplorasi Pengaruh Metode Giving Terhadap Keterlibatan Siswa dalam Pembelajaran di Sekolah Menengah Kejuruan - Fatahillah, Muhamad Arjuna; Ichwanto, Muhammad Aris; Sudarto, Sudarto (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines how the giving method impacts student engagement in education at Vocational High Schools (SMK). Using a qualitative approach with case studies, it was found that the Giving approach increased student engagement physically, emotionally, and cognitively. Students became more active, more motivated, and better understood what they were doing. Despite issues such as limited facilities and varying student participation, teachers said classroom interactions were better. The Giving method, which addresses existing issues, has been shown to improve student engagement and learning outcomes.